2007
DOI: 10.1007/s11207-007-9000-z
|View full text |Cite
|
Sign up to set email alerts
|

Solar Oscillation Frequency Changes on Time Scales of Nine Days

Abstract: We establish that global solar p-mode frequencies can be measured with sufficient precision on time scales as short as nine days to detect activity-related shifts. Using ten years of GONG data, we report that mode-mass and error-weighted frequency shifts derived from nine days are significantly correlated with the strength of solar activity and are consistent with long-duration measurements from GONG and the SOHO/MDI instrument. The analysis of the year-wise distribution of the frequency shifts with change in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 19 publications
4
30
0
Order By: Relevance
“…The mean frequency shifts normalized with mode inertia are determined as the difference between the frequencies of corresponding modes observed on different epochs and the average frequency over the entire period using Eq. (2) of Tripathy et al (2007). The frequency shifts in the frequency range of 2000 μHz ν 3500 μHz are shown in Fig.…”
Section: Analysis and Resultsmentioning
confidence: 94%
“…The mean frequency shifts normalized with mode inertia are determined as the difference between the frequencies of corresponding modes observed on different epochs and the average frequency over the entire period using Eq. (2) of Tripathy et al (2007). The frequency shifts in the frequency range of 2000 μHz ν 3500 μHz are shown in Fig.…”
Section: Analysis and Resultsmentioning
confidence: 94%
“…It may thus be surprising if there is anything new to learn in this area, but recent work using very short nine-day time series has revealed a more complex relationship between the mode frequencies and the surface field. Tripathy et al (2007) have shown that the slope of the linear relationship between ν and various activity indices varies with time and the phase of the solar cycle, as seen in Fig. 7.…”
Section: The Futurementioning
confidence: 87%
“…The acoustic frequencies can be affected by different phenomena associated to both weak and strong components of the magnetic field [e.g. [7][8][9][10]. Those may contribute to the observed frequency shifts through indirect (thermal and structural) effects and direct (via Lorentz force) effects.…”
Section: Introductionmentioning
confidence: 99%